ENVIRONMENTAL IMPACT EVALUATION ON CONSTRUCTION MATERIALS WITH THE INTEGRATION OF BUILDING INFORMATION MODELING (BIM) AND LIFE CYCLE ASSESSMENT (LCA) - Riska Ayu Febriyani; Indradi Wijatmiko; Wisnumurti Wisnumurti (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2021)
Technological developments, especially in the construction sector, have developed rapidly. The construction industry is one of the activities that consume energy, resources, and affects the environment. Therefore it is important to increase innovation and solutions to achieve sustainability standards. Several efforts were made to maintain environmental sustainability against global problems, namely the selection of building materials through an analysis of the impact of building materials on the environment called a Life Cycle Assessment (LCA). In this study, two types of curtain wall system materials, type (A), reinforced concrete, final coating, and type (B) brick, reinforced concrete, ceramic, and mortar will be compared. The method used in the completion of this research is a full building supply system in one way, namely the collaboration between Autodesk Revit and Tally which will then be analyzed again. The first step is to determine the type of material by calculating the total material requirements to be used or by modeling the building using Autodesk Revit. From the total volume of material that will be analyzed the impact of the building life cycle based on ISO 14040. The final objective of this research is to get the best alternative from the second material above. The results of the analysis supported the type (B) material which has a smaller effect than the type (A) material on the main environment that regulates global.